Supporting men through their transition to fatherhood with messages delivered to their smartphones: a feasibility study of SMS4dads - Richard Fletcher; Francis Kay-Lambkin; Chris May; Christopher Oldmeadow; John Attia; Lucy Leigh (BMC, 2017)
Abstract Background The transition to parenthood can be a challenging time, in which both mothers and fathers experience increased risk of distress and depression. Mothers are more likely than fathers to engage with services and have their mental health monitored and attended to during the perinatal period. The present study aimed to explore whether smartphone technology could be used to address fathers' needs across their transition to fatherhood. Methods A corpus of messages, including linked information and mood tracking software, was designed to support and enhance paternal relationships with their babies, their partners and themselves across the perinatal period. Messages were sent to project participants (N = 520) from 12-weeks' gestation to 24-weeks after birth. Results Of those fathers enrolled (N = 520), 21.5% scored >13 on K6 and completion rate (85%) was similar between these and other fathers. Most fathers (63.1%) clicked at least one link and responses were received for 20.5% of mood tracker questions. The probability of reporting worse mood scores decreased over time. Fathers completing post study surveys (N = 101) reported that messages helped them in their experience of becoming a new dad (92.8%), as well as helping them develop a strong relationship with their new child (54.9%), and in their relationship with their partner (79%). Conclusions The present study has demonstrated that it is both feasible and acceptable to support new fathers with SMS4dads, a relationship-focused messaging system designed to be delivered to smartphones across fathers' transition to parenthood.